2022
DOI: 10.1038/s42003-022-03453-2
|View full text |Cite|
|
Sign up to set email alerts
|

The Pel polysaccharide is predominantly composed of a dimeric repeat of α-1,4 linked galactosamine and N-acetylgalactosamine

Abstract: The genetic capacity to synthesize the biofilm matrix exopolysaccharide Pel is widespread among Gram-negative and Gram-positive bacteria. However, its exact chemical structure has been challenging to determine. Using a Pseudomonas aeruginosa strain engineered to overproduce Pel, improvements to the isolation procedure, and selective hydrolysis with the glycoside hydrolase PelAh, we demonstrate that Pel is a partially de-N-acetylated linear polymer of α-1,4-N-acetylgalactosamine comprised predominantly of dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…As P. aeruginosa swims, it deposits Psl trails that enhance the surface motility of subsequent cells, aiding in the formation of microcolonies [30,31. Sensing Psl further stimulates biofilm development by increasing levels of an important intracellular secondary messenger, cyclic di-guanosine monophosphate (cGMP) [32,33,34]. As the biofilm matures, Psl provides structural integrity by cross-linking CdrA, an extracellular adhesin, and eDNA [21,[35][36][37]. Psl limits the penetration of antibiotics by sequestration, and weakens host immunity by preventing efficient complement deposition, thereby inhibiting the production of neutrophil reactive oxygen species (ROS) and efficient phagocytosis of P. aeruginosa [38].…”
Section: Psl and Pelmentioning
confidence: 99%
See 1 more Smart Citation
“…As P. aeruginosa swims, it deposits Psl trails that enhance the surface motility of subsequent cells, aiding in the formation of microcolonies [30,31. Sensing Psl further stimulates biofilm development by increasing levels of an important intracellular secondary messenger, cyclic di-guanosine monophosphate (cGMP) [32,33,34]. As the biofilm matures, Psl provides structural integrity by cross-linking CdrA, an extracellular adhesin, and eDNA [21,[35][36][37]. Psl limits the penetration of antibiotics by sequestration, and weakens host immunity by preventing efficient complement deposition, thereby inhibiting the production of neutrophil reactive oxygen species (ROS) and efficient phagocytosis of P. aeruginosa [38].…”
Section: Psl and Pelmentioning
confidence: 99%
“…Pel is a cationic polymer important for biofilm formation, specifically pellicle development at the air-liquid interface, and like Psl, it is primarily associated with non-mucoid P. aeruginosa biofilms [45,46]. Pel is synthesized by proteins expressed by the pel operon (pelA -G), and structurally, it is composed of galactosamine and N-acetyl galactosamine residues linked by partially de-N-acetylated alpha 1-4 glycosidic linkages [47]. In strains that rely on Pel for biofilm formation, such as PA14, the EPS acts as a primary scaffold, maintaining cell-to-cell interactions between bacterial cells in a similar fashion as Psl in PAO1 [36,[48][49][50].The positively charged Pel has been observed to cross-link the negatively charged eDNA through ionic interactions, conferring tolerance against positively [39,51].…”
Section: Psl and Pelmentioning
confidence: 99%
“…The chemical structure and composition of Pel were unclear for a long time. Recent studies have suggested that Pel is a cationic exopolysaccharide with partially de- N -acetylated 1,4-linked N -acetylgalactosamine ( 102 , 103 , 104 ). The nonmucoid and mucoid isolates of P. aeruginosa secrete Psl, which is a polymer of pentasaccharide repeating units consisting of D-mannose, D-glucose, and L-rhamnose ( 103 , 105 ).…”
Section: Enzymatic Degradation Of Polysaccharides—an Emergent Approac...mentioning
confidence: 99%
“…A previously reported analysis of Pel polymer suggested that it is rich in cationic amino sugars, N-acetylgalactosamine, and N-acetylglucosamine, in a 5:1 ratio [ 52 ]. However, just recently, Le Mauff et al [ 53 ] characterized the configuration and structure of Pel and suggested that it is a polymer of partially de-N-acetylated α-1,4-N-acetylgalactosamine, and it does not contain N-acetylglucosamine.…”
Section: Biosynthesis Of Extracellular Polysaccharides In P...mentioning
confidence: 99%